An eccentric ankle heel drop into dorsiflexion as opposed to neutral causes more Achilles tendon tissue displacement, but not more non‐uniformity. Issue 6 (27th July 2021) - Verbeke, Léonie; de Brito Carvalho, Catarina; Ampe, Noémie; Peers, Koen; Bogaerts, Stijn
Abstract: To evaluate whether an adapted exercise regimen changes the intratendinous behavior of the Achilles tendon, comparing 2 variations of mechanical loading exercises: (i) heel drop with dorsiflexion (DF) and (ii) heel drop without dorsiflexion (N). Nineteen participants, 11 men and 8 women, mean age of 28 years, were included in the study. An ultrasound‐based speckle tracking technique was used to measure the mean local tendon tissue displacement of the different layers of the Achilles tendon during exercises DF and N. During acquisition, the edge of the calcaneus was always in sight at the outer edge of the image, leaving the rest of the image filled with pre‐insertional Achilles tendon. All statistics were performed using SPSS. During DF, there was a significantly greater displacement of the Achilles tendon than during N: 3.46 mm vs 2.61mm ( P < .05). The amount of non‐uniformity, that is, the relative difference in displacement between tendon layers, between both groups (DF and N) showed no significant difference. Changing the exercise regimen in accordance to the location of the structural abnormalities in the Achilles tendon (eg, insertional vs midportion) may have better clinical outcomes in comparison with the "one size fits all" eccentric heel drop.